The relationship between acquired resistance and transmission of Schistosoma Weinland, 1858, in man and its influences on the prevalence of S Capense (Harley, 1864) and S Mansoni Sambon, 1907, in Southern Rhodesia - Clarke, H V de V (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1965)
Bilharziasis ranks with Tuberculosis and Malaria as the three most important endemic diseases of man in Rhodesia. The prominence given to bilharziasis in the endemic diseases pattern arises from its high prevalence, particularly in the African population. It is probable that bilharziasis was endemic in the country even prior to the arrival in the conntry of the European settlers in 1890, but it was not until Orpen (1915) described the results of a small survey that local infections were proven. He reported 182 (31 percent) urinary infections in 592 African prisoners examined in the Salisbury gaol. In the ensuing 15 years there was only scanty evidence of the prevalence of the disease. However, in the decade 1931 to 1940 the Annual Public Health Reports of Southern Rhodesia indicated increasing prevalence, and this stimulated interest in the problem and led to the establishment in 1939 of a specialised laboratory to study the parasites causing the disease. The unpublished records of this laboratory indicate that in more recent years the disease has increased not only in prevalence but also in its intensity in infected individuals. Surveys show that the urinary form of the disease is more widespread than the intestinal form. Both forms are becoming more prevalent but the rapid increase of the latter, considered by most authorities to be the more severe, indicates that a greater importance must be accorded to it in the future. Introduction, p. 1.
Keywords: Platyhelminthes; Schistosoma; Schistosomiasis